Reasons and means for involvement with Heinrich Schenker's proposal (Orfeu, 2021)
The expansion of the three-dimensional perception of musical works that emerges from the contact of musicians with the Schenkerian proposal is valued in this article. To this end, the authors share with the reader their experience with the teaching of this interpretative practice, in dialogue with harmonic, contrapuntal and textural processes.
Keywords: Heinrich Schenker; Musical motif; Musical counterpoint; Musical harmony; Musical multilevel graphic